Hepatic macrophages in liver fibrosis: pathogenesis and potential therapeutic targets - Hai Li; Hong You; Jidong Jia; Xu Fan (BMJ Open Gastroenterology)
Hepatic macrophages account for the largest non-parenchymal cell population in the liver. Recent studies have found that hepatic macrophages have different functions in different stages of experimental liver fibrosis. Some studies found that there are different types of hepatic macrophages in the liver, although others have suggested that hepatic macrophages could switch to different phenotypes in different environments. Many studies demonstrated that while hepatic macrophages promoted fibrosis through the recruitment of proinflammatory immune cells, and the secretion of proinflammatory cytokines and chemokines in the early stages, these also promoted the resolution of hepatic fibrosis through the secretion of matrix metalloproteinases in the late stages. This article will review the current role played by hepatic macrophages in liver fibrosis and the potential therapeutic targets that modulate hepatic macrophages.